Progress in Black Titania: A New Material for Advanced Photocatalysis. Issue 17 (27th June 2016) - Liu, Xiangye; Zhu, Guilian; Wang, Xin; Yuan, Xiaotao; Lin, Tianquan; Huang, Fuqiang
Abstract : The photocatalytic activity of TiO2 has aroused a broad range of research effort since 1972. Although TiO2 has a very high efficiency in utilizing ultraviolet light, its overall solar activity is very limited due to its wide bandgap (≈3.0−3.2 eV). This is a bottleneck for TiO2 to be applied in the areas ranging from visible‐light photocatalysis and photovoltaics to photo‐electrochemistry and sensors. Recently, the emergence of black TiO2 nanomaterial has triggered world‐wide research interest, because of its substantially enhanced solar absorption and the improved photocatalytic activities. Here, a variety of synthetic strategies of black TiO2 are outlined, and the structural and chemical features, band structures and electronic properties of the black TiO2 nanomaterials are described in details, along with their photocatalytic performances as well as some other new applications. Abstract : Black TiO2 nanomaterials have aroused world‐widely scientific interests, owing to their enhanced optical absorption properties and promising visible‐light photocatalysis. The recent progress in the research of black TiO2 is reviewed here, including their synthetic approaches, crystal structure and chemical characters, unique band structure and electronic properties, and their photocatalytic and photovoltaic applications.